2021
DOI: 10.1029/2021ja029475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interplanetary Magnetic Field on Hemispheric Asymmetry in Ionospheric Horizontal and Field‐Aligned Currents During Different Seasons

Abstract: Effect of interplanetary magnetic field on hemispheric asymmetry in ionospheric horizontal and field-aligned currents during different seasons.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…Regarding the overall higher degree of symmetry exhibited by total Birkeland and divergence-free currents in each hemisphere for B z < 0 relative to B z > 0, Workayehu et al (2021) draw essentially the same conclusion using Swarm satellite measurements, but a rather different methodology based on spherical elementary currents. Regarding the overall variation of the NH/SH ratio of total Birkeland current with season, Workayehu et al (2020) also find that NH total Birkeland current is greater by about 20% during local winter.…”
Section: With Respect To Dependence On Imf Orientation Bothmentioning
confidence: 55%
“…Regarding the overall higher degree of symmetry exhibited by total Birkeland and divergence-free currents in each hemisphere for B z < 0 relative to B z > 0, Workayehu et al (2021) draw essentially the same conclusion using Swarm satellite measurements, but a rather different methodology based on spherical elementary currents. Regarding the overall variation of the NH/SH ratio of total Birkeland current with season, Workayehu et al (2020) also find that NH total Birkeland current is greater by about 20% during local winter.…”
Section: With Respect To Dependence On Imf Orientation Bothmentioning
confidence: 55%
“…Recent studies have revealed that IMF B y effects are complex and seasonally varying, showing dependence on the dipole tilt angle. The combined dependence on IMF B y and the dipole tilt (also called the explicit B y ‐dependence) strongly modulates auroral electrojets (Friis‐Christensen et al., 2017; Holappa & Mursula, 2018; Holappa et al., 2021; Workayehu et al., 2021), electron precipitation (Holappa et al., 2020), and the size of polar cap (Reistad et al., 2020). These effects are quite significant, for example, showing variations in the AL index up to 40% for opposite values of B y .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a negative IMF B y component results in larger nightside auroral intensity in the Northern Hemisphere (NH; Liou et al., 1998; Shue et al., 2001) while the effect is reversed in the southern hemisphere (Liou & Mitchell, 2019). On dayside, the postnoon auroral bright spot is brighter for negative IMF B y than for positive IMF B y and the effect is reversed in the southern hemisphere (Liou & Mitchell, 2019) Also several studies (Friis‐Christensen et al., 1972, 2017; Holappa & Mursula, 2018; Murayama et al., 1980; Smith et al., 2017; Workayehu et al., 2021; Holappa et al., 2021) have shown that there is a strong IMF B y ‐dependence in auroral currents which is not symmetric with the B y sign. This so‐called explicit B y ‐dependence is especially strong in the AL index (measuring the westward electrojet), which is about 40% stronger for B y > 0 than for B y < 0 in NH winter, or under negative tilt angle of the Earth's magnetic dipole with respect to the Sun‐Earth line.…”
Section: Introductionmentioning
confidence: 96%
“…Workayehu et al. (2021) compared the distributions of the auroral current density in different seasons for four IMF clock angles, and found that the field‐aligned current density near the cusp region is quite larger for negative B y in northern summer. They suggested that the influence of the IMF B y on the auroral current systems depends on the season, which is essentially consistent with ours.…”
Section: Discussionmentioning
confidence: 99%
“…These results illustrate that the 2-nT deviation of the IMF |B y | is an average effect of the season, which implies that the IMF controlling effects on the cusp auroral intensity can be affected by the season. Workayehu et al (2021) compared the distributions of the auroral current density in different seasons for four IMF clock angles, and found that the field-aligned current density near the cusp region is quite larger for negative B y in northern summer. They suggested that the influence of the IMF B y on the auroral current systems depends on the season, which is essentially consistent with ours.…”
Section: The Interhemispheric Asymmetry and Seasonal Dependence Of Th...mentioning
confidence: 99%